HPLC-DAD PROFILING OF SIDR LEAVES AND ROASTED CANDLENUT FOR ALOPECIA THERAPY - Elfasyari, Trie Yuni; Zulfisa; Mevy Trisna (JURNAL KATALISATOR, 2025)
Alopecia is a dermatological disorder characterised by progressive hair loss, often impairing patients’ quality of life. Conventional therapies, such as minoxidil and finasteride, have demonstrated efficacy; however, their adverse effects have prompted the search for natural-based alternatives. Sidr leaves (Ziziphus spina-christi L.) and roasted candlenut seeds (Aleurites moluccanus L.) have been traditionally employed in ethnopharmacology for hair treatment, yet scientific data on their phytochemical composition remain limited. This study aimed to identify and quantify the major bioactive constituents in purified aqueous extracts of sidr leaves and roasted candlenut seeds using high-performance liquid chromatography coupled with diode-array detection (HPLC-DAD), and to assess their potential implications in alopecia therapy. Powdered sidr leaves and roasted candlenut seeds were extracted, fractionated, and analysed on a C18 column using a gradient acetonitrile–water mobile phase. The results revealed that sidr leaves are rich in rutin hydrate (245.64 ± 0.73 mg/L), accompanied by gallic acid (47.63 ± 0.43 mg/L) and quercetin (6.85 mg/L), whereas roasted candlenut seeds predominantly contain quercetin (27.00 mg/L). Rutin functions as an antioxidant and angiogenesis stimulator, gallic acid exhibits anti-inflammatory activity, and quercetin acts as a 5α-reductase inhibitor relevant to androgenetic alopecia. In conclusion, the phytochemical profiles of sidr leaves and roasted candlenut seeds support their potential use as phytotherapeutic candidates for alopecia management.